Structure, Mechanism, and Application of Vacuum Insulation Panels in Chinese Buildings - Changhai Peng; Jianqiang Yang (Advances in Materials Science and Engineering)
Thermal insulation is one of the most used approaches to reduce energy consumption in buildings. Vacuum insulation panels (VIPs) are new thermal insulation materials that have been used in the domestic and overseas market in the last 20 years. Due to the vacuum thermal insulation technology of these new materials, their thermal conductivity can be as low as 0.004 W/(m·K) at the center of panels. In addition, VIPs that are composites with inorganic core and an envelope out of commonly three metallized PET layers and a PE sealing layer can provide B class fire resistance (their core materials are not flammable and are classified as A1). Compared with other conventional thermal insulation materials, the thermal insulation and fire resistance performances form the foundation of VIP’s applications in the construction industry. The structure and thermal insulation mechanism of VIP and their application potential and problems in Chinese buildings are described in detail.